2016
DOI: 10.3389/fneur.2016.00022
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine Deiminases as Drug Targets in Neonatal Hypoxic–Ischemic Encephalopathy

Abstract: Oxygen deprivation and infection are major causes of perinatal brain injury leading to cerebral palsy and other neurological disabilities. The identification of novel key factors mediating white and gray matter damage are crucial to allow better understanding of the specific contribution of different cell types to the injury processes and pathways for clinical intervention. Recent studies in the Rice–Vannucci mouse model of neonatal hypoxic ischemia (HI) have highlighted novel roles for calcium-regulated pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 132 publications
(150 reference statements)
1
22
0
Order By: Relevance
“…Previous studies on in vivo models of CNS damage showed that PAD-upregulation and increased protein deimination lead to vast neuronal death which was preventable by pharmacological PAD inhibition, significantly reducing neuroinflammatory responses and histone H3 deimination, which has implications in gene regulation [23,[33][34][35]. In addition we have observed increased PAD expression during disease progression in tau mutation mouse models compared to age-matched controls [36].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies on in vivo models of CNS damage showed that PAD-upregulation and increased protein deimination lead to vast neuronal death which was preventable by pharmacological PAD inhibition, significantly reducing neuroinflammatory responses and histone H3 deimination, which has implications in gene regulation [23,[33][34][35]. In addition we have observed increased PAD expression during disease progression in tau mutation mouse models compared to age-matched controls [36].…”
Section: Introductionsupporting
confidence: 53%
“…Increased EV shedding from cancer cells, facilitated in part by upregulated PAD expression, also acts as a protective mechanism of cancer cells to expel chemotherapeutic drugs. Functional roles for PADs in CNS damage, and neuroprotective pharmacological intervention in vivo, have recently been established and provide evidence for crucial roles of PAD-mediated mechanisms in neuroinflammation [32][33][34][35]. Pilot studies using human iPSC neuronal models, derived from patients' fibroblasts carrying neurodegenerative disease mutations, show increased PAD activity and PAD-mediated deimination that will also affect downstream EV release [36].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of deiminated histone H3 were here observed in the dentate gyrus as well as in cortex of the pre-motor PD brains. Such increase in citH3 positive detection may be of considerable importance in the neuroinflammatory environment; indeed, previous studies of CNS injury, including via hypoxic damage, have shown that pharmacological inhibition of PADs, and associated reduction of citH3, correlates with neuroprotective effects [119][120][121].…”
Section: Discussionmentioning
confidence: 95%
“…Hypoxia related pathways may be of considerable relevance due to the hypoxic core of a tumour mass, which also contains the therapy resistant glioma stem-like cells, a well-recognized problem in the standard treatment of GBM tumours [10,11]. PAD activation has indeed been linked to hypoxia in the CNS [53][54][55] and deiminated KEGG (Kyoto Encyclopedia of Genes and Genomes) protein pathways for HIF-1 regulation have been identified to be enriched in animal models of hypoxia-and cancer-resistance [56,57]. PADs also modulate neuronal stem cell growth and death [58], which is of importance considering that GBM tumour invasion, progression and chemo-resistance of recurrent GBM are partly linked to stem-ness [59,60].…”
Section: Introductionmentioning
confidence: 99%